A Model Study on the Carbon‐Halogen Activation in Perhalonated Arenes with Isonitrile Under Photoirradiation. Issue 8 (6th June 2016) - Su , Ming‐Der
Abstract: The mechanisms of the photochemical carbon‐halogen bond activation reactions were investigated theoretically using a model system of hexahalobenzene C6X6 (X=F, Cl, and Br) and phenyl isonitrile (PhN=C:), with the M06‐2X method and the 6–311G(d) basis set. The theoretical findings suggest the photoactivation mechanism should proceed as follows:Rea‐X‐S0 + hν →FC‐X‐T1 →PhNC‐T1 + C6X6 →Int‐X‐T1 →TS‐X‐T1 →T1/S0‐X →Pro‐X‐S0 . The present theoretical evidence confirms the reported results by Studer and co‐workers that using UV irradiation, a simple and efficient transition‐metal‐free C‐F activation in various perfluoroarenes with aryl and alkyl isonitriles obtain imidoyl fluorides. Nevertheless, due to the highly vertical Frank‐Condon excitation energy, our theoretical study demonstrates N‐heterocyclic carbene cannot undergo the C‐F bond activation reaction with hexafluorobenzene under photoirradiation, which closely agrees with the available experimental observations. The present theoretical research reveals the spin crossover processes, which lead to a concerted reaction pathway, play a key role in the regioselecitivities of the final photoinsertion products. Abstract : The present theoretical findings suggest under UV photoirradiation, one C‐X bond of C6X6 can be readily activated by phenyl isonitrile to produce imidoyl halides with high regioselectivity. On the other hand, our theoretical evidence demonstrates N‐heterocyclic carbene (NHC) cannot undergo the C‐F bond activation reaction with hexafluorobenzene under photoirradiation due to the high vertical excitation energy of NHC.